Assigning the stereochemical structures of aurantinin A and B with the assistance of biosynthetic investigations. Issue 21 (26th September 2022) - Wang, Dacheng; Li, Pengwei; Yan, Jia-Lei; Mao, Huijin; Liu, Lilu; Wang, Min; Chen, Meng; Ye, Tao; Chen, Yihua
Abstract : The stereochemistry of aurantinin was determined by spectroscopic and computational analysis with the assistance of biosynthetic studies. The latter method provided critical evidence for the assignment of the configuration of the 3-ketosugar moiety. Abstract : Aurantinins (ARTs) are a group of antibacterial polyketides featuring a 6/7/8/5-fused tetracyclic ring system and a triene alkyl chain with a carboxylic terminus. Previous studies assigned their planar structures and proposed ART B as 17- O -glycosylated ART A with a rare 3-keto sugar. In this work, the stereochemical structures of ARTs A and B were assigned by combining the spectroscopic and computational methods with biosynthetic studies. Biosynthetic investigations aided in the assignment of ART A's absolute configuration and provided critical evidence for determining the configuration of ART B's 3-ketosugar moiety, demonstrating that appropriate biosynthetic investigations can be very useful in resolving the complicated structures of certain natural products.